Assessing effects of drought on tree mortality and productivity in European forests across two decades: a conceptual framework and preliminary results. Issue 1 (December 2021) - George, Jan-Peter; Neumann, Mathias; Vogt, Jürgen; Cammalleri, Carmelo; Lang, Mait
Abstract: Forests are currently experiencing an unprecedented period of progressively drier growing conditions around the globe, which is threatening many forest ecosystem functions. Trees as long-living organisms are able to withstand drought periods. Our understanding on critical drought severity resulting in substantial decline in net primary productivity and/or eventually tree mortality is underdeveloped. A wide range of remote sensing products and ground observations, including information on productivity, tree vitality, climate, and soil moisture with high temporal and spatial resolution are now available. Linking these data sources could improve our understanding of the complex relationship between forest growth and drought. We introduce here a conceptual framework using satellite remotely sensed net primary productivity (MOD17A3 and MODIS EURO), ground observations of tree mortality (ICP level I survey data), soil moisture anomaly (Copernicus European Drought Observatory), and spatially-downscaled daily climate data for entire Europe. This unique analysis will enable us to test the influence of biotic and abiotic covariates such as tree age, stand history, and drought legacy using historic droughts for model development. This conceptual framework, as evident from the preliminary results shown here, can help anticipating the effects of future droughts and optimize global climate models considering drought effects.